Endothelial-Specific Deletion of CD146 Protects Against Experimental Glomerulonephritis in Mice. Issue 4 (April 2021) - Abed, Ahmed; Leroyer, Aurélie S.; Kavvadas, Panagiotis; Authier, Florence; Bachelier, Richard; Foucault-Bertaud, Alexandrine; Bardin, Nathalie; Cohen, Clemens D.; Lindenmeyer, Maja T.; Genest, Magali; Joshkon, Ahmad; Jourde-Chiche, Noémie; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : CD146 is an endothelial junctional adhesion molecule, which expression is increased in human glomerular diseases. However, the pathological significance of this overexpression remains unknown. Induction of glomerulonephritis in mice, by using nephrotoxic serum, showed that CD146 expression was highly induced within damaged glomeruli and was associated with renal inflammation and fibrosis. Interestingly, 2 weeks after glomerulonephritis induction, CD146 knockout mice showed preserved renal function as proteinuria and blood urea nitrogen levels were significantly lower compared with wild-type littermates. Furthermore, renal structure was considerably conserved, since crescents formation, tubular dilation, monocyte and lymphocyte infiltration, and interstitial renal fibrosis were highly reduced. Colocalization with markers for different types of glomerular cells showed that CD146 expression was mainly increased within the injured endothelium of the glomerular tuft. Consequently, we generated a new transgenic strain in which CD146 was specifically deleted in the vascular endothelium. Similarly to CD146 knockout, these mice showed preservation of renal structure and function after the induction of glomerulonephritis compared with wild-type animals. These data show that endothelial CD146 plays a major role in glomerulonephritis and may represent a novel therapeutic target to reduce glomerular damage and the progression of renal disease.